The new governance of religious diversity - Modood, Tariq 1952-; Sealy, Thomas (Polity, 2024)
"Religious diversity is a key feature of countries across the globe today, but it also presents governments with very real challenges. In this book Modood and Sealy unravel this complex phenomenon, drawing on original research to present new ways of analysing and enhancing the governance of religious diversity world-wide"--
Keywords: Cultural pluralism; Freedom of religion